Kepemimpinan Kepala Sekolah untuk Mewujudkan Sekolah sebagai Wadah Moderasi Beragama: Kepemimpinan Kepala Sekolah untuk Mewujudkan Sekolah sebagai Wadah Moderasi Beragama - An nadya, Saffina Muzdalifa; nikmatulloh, nizwatul; Fathoni, Tamrin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Abstract The leadership of school principals plays a vital role in creating a harmonious and moderate educational environment, particularly in Indonesia, which is rich in cultural and religious diversity. This study aims to explore the strategies and challenges faced by school principals in realizing religious moderation within educational institutions. Using a qualitative approach and literature review, this research analyzes the literature discussing the role of school principals in integrating values of tolerance and religious moderation. The findings indicate that school principals can instill tolerance values through inclusive policies, build a curriculum based on religious moderation, create a harmonious school environment, and serve as role models for moderate attitudes. The results of this study are expected to contribute to the development of education in Indonesia and support efforts to create a more tolerant and harmonious society.